(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: Congenital cardiac defect is the major cause of mortality and morbidity in our country but maximum cases are undetected due to lack of skill, shortage of man power, modern equipment in peripheral hospitals. But simply observing murmur can give us the clue for underlying congenital heart diseases. Objectives: The purpose of this study is to determine the incidence and clinical significance of cardiac murmur in neonates in a tertiary level hospital in Rajshahi. Methods: This cross-sectional descriptive study was done in neonates (age ≤ 28 days) in Rajshahi Medical College Hospital from January 2014 to December 2015. Results: during this study period total 4120 neonates were admitted in neonatal ward and only 52 cases were presented with cardiac murmur clinically. Incidence rate of murmur was 1.26%. Among 52 cases 40 cases were having pathological murmur and 12 cases were having innocent murmur. After doing echocardiogram 34 cases were showing structural cardiac defect out of 40 pathological murmur and 4 cases were showing structural cardiac defect out of 12 innocent murmur. Total cases of structural cardiac defect (congenital heart disease) were 38(34+4). So, incidence of congenital heart disease was 9.22/ 1000 live births. Conclusion: Congenital cardiac defect is the major cause of mortality and morbidity in our country but maximum cases are undetected during neonatal period but simply observing murmur can give us the clue for underlying congenital heart diseases in 73.08% cases (38 were congenital heart disease out of 52 cases). If congenital heart disease is early detected and properly managed many valuable lives of neonates can be saved and their growth and development will be smooth. TAJ 2017; 30(2): 54-59